The Moderating Effect Of Organizational Culture On The Relationship Between Leadership Styles And Job Performance Of Service Sector In Kuching, Sarawak - Tan, Deanna Yi Cheing (Universiti Malaysia Sarawak, (UNIMAS), 2019)
This research is attempted to investigate the moderating effect of organizational culture between the relationship of leadership styles and job performance. Based on this research, leadership styles (transformational, transactional and bureaucratic) are used to predict the employee's behavior in the aspect of job performance. Meanwhile, organizational culture is taken into the research as a moderator. There is total of six hypotheses which are formed and investigated with the employees from service sectors in Kuching, Sarawak, as the respondents for this research. The data collected from respondents is in a form of 5-point Likert Scale questionnaires. The outcome of the study indicate that transformational leadership has significant positive impact toward employees' job performance. Meanwhile, organizational culture has a moderating effect toward transformational leadership styles and employees' job performance.